Enhancing nurses’ clinical decision-making confidence through dual pathways of self-directed learning: A structural equation model - Liya Wu; Mengyu Zhang; Juan Ye (PLoS ONE, 2026)
Background Nurses operate in complex clinical environments demanding autonomous judgment, emotional regulation, and interpersonal collaboration, yet the mechanisms through which psychological and learning resources support clinical decision-making confidence remain inadequately characterized. Objective To examine the dual mediating roles of cognitive and relational self-directed learning in the relationship between emotional intelligence and clinical decision-making confidence among registered nurses. Design Cross-sectional survey study. Setting Multiple medical schools and affiliated teaching hospitals across Eastern, Central, and Western China. Participants 1,478 registered nurses recruited via convenience sampling between June and August 2025. Methods Emotional intelligence was assessed using the Wong and Law Emotional Intelligence Scale, self-directed learning via a reorganized two-factor version of the Self-Rating Scale of Self-Directed Learning, and clinical decision-making confidence via the Clinical Decision-Making Self-Confidence Scale. Structural equation modeling with bias-corrected bootstrapping (5,000 resamples) tested the mediation hypotheses. Results Emotional intelligence significantly predicted both cognitive self-directed learning (β = 0.643, p < 0.01) and relational self-directed learning (β = 0.601, p < 0.01), as well as clinical decision-making confidence in both models. In the model with cognitive self-directed learning as mediator, the indirect effect was 0.339 (95% CI [0.273, 0.409]), representing 71.8% of the total standardized effect. In the separate model with relational self-directed learning as mediator, the indirect effect was 0.241 (95% CI [0.185, 0.302]), representing 50.8% of the total standardized effect. Both pathways were statistically significant. Conclusions Both cognitive and relational self-directed learning are significant mediators of the relationship between emotional intelligence and clinical decision-making confidence. These findings support integrating emotional intelligence training with self-directed learning development in nursing education programs.